The Migraine Postdrome. Issue 4 (August 2018) - Bose, Pyari; Karsan, Nazia; Goadsby, Peter J.
ABSTRACT: PURPOSE OF REVIEW: The migraine postdrome is the least studied and least understood phase of migraine. This article covers the salient features of the migraine postdrome and provides insight into the history, clinical symptoms, and future implications of this phase of migraine. RECENT FINDINGS: Prospective electronic diary studies have shown that patients are left disabled with various nonheadache symptoms in the migraine postdrome, and 81% of patients report at least one nonheadache symptom in the postdrome. Hence, it is important to understand this phase better and ensure that more effective treatments become available in the future to lessen the morbidity associated with this phase. Functional imaging shows widespread reduction in brain-blood flow in the postdrome, which explains the multitudes of symptoms experienced by patients. SUMMARY: The disability related to migraine is not exclusive to the headache phase but extends into the postdrome phase and is associated with several nonheadache symptoms that prolong the symptoms experienced by patients with migraine. Further research into the postdrome is crucial to improve our overall understanding of migraine mechanisms. This knowledge may also help to treat the concurrent nonheadache symptoms better in the future. Novel neuroimaging techniques provide a valuable noninvasive tool to push the frontiers in the understanding of migraine pathophysiology. These methods may help shed further light onto the possible links between key brain structures and networks that could be implicated in the pathophysiology of the various migraine phases.